2021
DOI: 10.5194/gmd-2021-175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A derivative-free optimisation method for global ocean biogeochemical models

Abstract: Abstract. The performance of global ocean biogeochemical models, and the Earth System Models in which they are embedded, can be improved by systematic calibration of the parameter values against observations. However, such tuning is seldom undertaken as these models are computationally very expensive. Here we investigate the performance of DFO-LS, a local, derivative-free optimisation algorithm which has been designed for computationally expensive models with irregular model-data misfit landscapes typical of b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Indeed, Kriest et al (2017) observed the most insensitive parameter subject to their optimization experiment to converge the slowest. The same behavior was recently observed by Oliver et al (2021) who applied an even faster (but less explorative) search algorithm to the same coupled BGC model setup, using twin experiment data. However, fixing some parameters from the start might impact the optimization of the other parameters.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Indeed, Kriest et al (2017) observed the most insensitive parameter subject to their optimization experiment to converge the slowest. The same behavior was recently observed by Oliver et al (2021) who applied an even faster (but less explorative) search algorithm to the same coupled BGC model setup, using twin experiment data. However, fixing some parameters from the start might impact the optimization of the other parameters.…”
supporting
confidence: 74%
“…The TMM represents advection and mixing in terms of transport matrices which are precomputed from an online ocean circulation model simulation. Here, as in Kriest et al (2017) and also in Oliver et al (2021), we apply monthly mean transport matrices from a 2.8° global configuration of the MIT general circulation model (MITgcm), having 15 depth levels (Marshall et al, 1997). MOPS coupled to the TMM simulates globally the concentrations and biogeochemical turnover of seven tracer components, namely phyto-and zooplankton, dissolved and particulate organic matter, phosphate, nitrate and oxygen.…”
Section: The Global Ocean Biogeochemical Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…CMA-ES has been shown to be a reliable and highly competitive evolutionary algorithm for both local (Hansen and Ostermeier, 2001) and global optimisation (Hansen and Kern, 2004;Hansen, 2009). It has been tested on real-world problems includ- ing parameter calibration in a biogeochemical ocean model by Kriest et al (2017), whose implementation of CMA-ES in C++ we employ here, via the OptClimSO package (https://doi.org/10.5281/zenodo.5517610; Tett et al, 2013;Oliver et al, 2022). In order to apply CMA-ES to a constrained problem, we use the boundary handling described in Hansen et al (2009), in which boundaries are imposed by adding a penalty function to the calculated misfit when a parameter's distribution mean is out of bounds.…”
Section: Optimisation Algorithmmentioning
confidence: 99%